Case study on open access journals in Economics and Business Studies and their engagement on the Web - Kaltrina Nuredini; Atif Latif; Isabella Peters (CERN; CERN, 2017)
In the beginning of 2001 Lawrence showed that Open Access (OA) papers have a citation advantage (Lawrence, 2001) over closed access articles. Since then several research studies have arrived at the same results (e.g., Archambault et al., 2015; Wang et al., 2015). According to Wang et al., (2015) OA citation entails more advantage by collecting more usage metrics and social media attention. In recent years altmetrics accumulated from social media are used and studied by researchers (Priem, 2011; Piwowar, 2013; Bornmann, 2014). Many interdisciplinary studies confirm that altmetrics reveal a different impact from citation nevertheless there's a positive and moderate correlation with each other (Costas et al., 2014; Nuredini & Peters, 2015). Altmetric information differentiates from a discipline to a discipline where the amount of papers found varies across social media sources. Nuredini and Peters (2015) reveal the top 3 most used altmetric sources (Mendeley, Twitter, News) for Economic and Business Studies (EBS) whereas Costas et al. (2014) outline that biomedical and health science publications are mostly found on Facebook, Twitter and Blogs. Since OA journals are free to read it is important to see whether openness can lead to more attention online in comparison with closed journals. Therefore the study looks at OA journals and their altmetric information in the field of EBS and aims at answering the following research questions: RQ1: What is the coverage of OA journal articles in EBS in Altmetric.com and what are frequent social media services generating altmetrics for EBS? RQ2: Do OA journals have more altmetric sources as compared to closed journals/articles? RQ3: Do papers with higher Altmetric.com scores possess higher citation counts and vice versa?
Conference: altmetrics17. The dependencies of altmetrics. The 2017 Altmetrics Workshop, Toronto, 26 September 2017
Keywords: 330; altmetrics; open access journals; economics; business studies; citations